Legal Protection for Victims of Revenge Porn Crimes: A Critical Analysis Based on Victimology Theory - Maharani, Nurrachma; Kholiq, Abdul (Dinasti Research, 2025)
The purpose of this study is to critically analyze the legal protection for victims of revenge porn crimes in Indonesia based on victimology theory. This study used normative legal research methods, applying a statutory and victimology approach. The findings indicate that the existing regulations do not specifically address revenge porn, resulting in many victims facing difficulties in obtaining justice. Furthermore, the phenomena of victim blaming and slut shaming exacerbate the victims' conditions and hinder legal proceedings. This study recommends more inclusive legal reforms with a victimology-based approach to ensure protection and recovery for revenge porn victims.